EFEKTIVITAS METODE STORYTELLING DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN UNTUK MENINGKATKAN CIVIC KNOWLEDGE SISWA KELAS VIII C SMP NEGERI 11 MUARO JAMBI - Imeliana, Arum; Hendra; Heri Usmanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of the storytelling method in improving students' civic knowledge in Civic Education (PPKn). The study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The research was conducted in class VIII C of SMP Negeri 11 Muaro Jambi involving 28 students selected through purposive sampling. Data were collected using pretest and posttest instruments that measured students' civic knowledge. Data analysis included validity testing, normality testing, the Wilcoxon Signed Rank Test, and N-Gain analysis. The findings revealed a significant improvement in students' civic knowledge after the implementation of the storytelling method. The Wilcoxon Signed Rank Test produced a significance value of less than 0.05, indicating a statistically significant difference between pretest and posttest scores. Furthermore, the N-Gain analysis showed that the improvement was categorized as moderate, demonstrating that storytelling effectively enhanced students' understanding of civic concepts. Therefore, storytelling can serve as an innovative and meaningful learning method to improve students' civic knowledge in Civic Education.